2014
DOI: 10.1684/epd.2014.0686
|View full text |Cite
|
Sign up to set email alerts
|

What is more harmful, seizures or epileptic EEG abnormalities? Is there any clinical data?

Abstract: Cognitive impairment is a common and often devastating co-morbidity of childhood epilepsy. While the etiology of the epilepsy is critical determinant of cognitive outcome, there is considerable evidence from both rodent and human studies that indicate that seizures and interictal epileptiform abnormalities can contribute to cognitive impairment. A critical feature of childhood epilepsy is that the seizures and epileptiform activity are occurring in a brain with developing, plastic neuronal circuits. The conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 126 publications
(182 reference statements)
0
29
0
Order By: Relevance
“…Wolf-Hirschhorn syndrome (WHS; Online Mendelian Inheritance in Man (OMIM) #194190) is a rare contiguous gene deletion syndrome affecting the terminal region of chromosome human chromosome 4, petite arm (4p) [1]. Epilepsy is a serious neurologic challenge for over 90% of individuals with WHS, presenting in early childhood and potentially affecting cognitive development [2]. A previous study involving 87 individuals with WHS determined that seizure types most commonly experienced are generalized tonic-clonic, tonic or clonic, and complex partial [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wolf-Hirschhorn syndrome (WHS; Online Mendelian Inheritance in Man (OMIM) #194190) is a rare contiguous gene deletion syndrome affecting the terminal region of chromosome human chromosome 4, petite arm (4p) [1]. Epilepsy is a serious neurologic challenge for over 90% of individuals with WHS, presenting in early childhood and potentially affecting cognitive development [2]. A previous study involving 87 individuals with WHS determined that seizure types most commonly experienced are generalized tonic-clonic, tonic or clonic, and complex partial [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among the co-morbidities associated with epilepsy in children, cognitive abnormalities are among the most common and troublesome 2,3 . The distribution of intelligence quotient (IQ) scores of children with epilepsy is skewed toward lower values 4,5 and the number of children with epilepsy experiencing difficulties in school because of learning disabilities is greater than children without epilepsy 611 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, more researchers are coming to this conclusion [40], yet clinical lore has long suggested that any effect is trivial and likely not worth considering. In this context, we believe that our current case examples, while not definitive proof of this concept, provide impetus for further study.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment appeared to be due to impairment of cell formation in the hippocampus. These findings raise the possibility that IEDs during early human development could have profound effects on later cognitive and behavioral function [40]. …”
Section: 3 Animal Research Related To the Effects Of Interictal Epmentioning
confidence: 99%